2018
DOI: 10.7575/aiac.alls.v.9n.3p.81
|View full text |Cite
|
Sign up to set email alerts
|

Need Analysis for Developing Translation’s Textbook base on TEFL Pedagogical Purpose in Indonesia: English Teachers’ Perspectives

Abstract: The purpose of this study was to find out the Prospective English teachers’ perspective on the development of translation’s textbook base on Teaching English as a Foreign Language (TEFL) Pedagogical purpose. Therefore, the quantitative research was applied to gather the data. By using the questionnaire with Likert Scale, the quantitative data were collected from 100 prospective English teachers in Indonesia. As a result, from nine aspects questioned to the prospective English teachers, most of them (92%) said … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(4 reference statements)
1
4
0
Order By: Relevance
“…Furthermore, there is a need to establish a connection between the educational context and the labor market. This finding was in line with the findings of the researchers which is conducted by Masitowarni and Sylvana [9]. The result of her study was found that; from nine aspects questioned to the potential English teachers, most of them (92%) said that the translation's textbook base on TEFL Pedagogical purpose was significantly needed.…”
Section: B Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, there is a need to establish a connection between the educational context and the labor market. This finding was in line with the findings of the researchers which is conducted by Masitowarni and Sylvana [9]. The result of her study was found that; from nine aspects questioned to the potential English teachers, most of them (92%) said that the translation's textbook base on TEFL Pedagogical purpose was significantly needed.…”
Section: B Discussionsupporting
confidence: 86%
“…In addition many researchers also conducted research about need analysis for developing translation text book in order to meet the gap between materials offered and market demands. They are: [9], [10]. [11] Discusses about theory in translator training: some observations about syllabus design.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, materials or teaching materials under the needs of students will make them more likely to acquire language skills (Aflah & Rahmani, 2018). By analyzing needs, teachers/lecturers can determine learning objectives, choose topics, and even change curriculum, procedures, and teaching methods (Siregar et al, 2018). Needs analysis leads to the development of teaching materials, curricula, and teaching methods that increase student motivation and success (Sulistiyo et al, 2021).…”
Section: Literatur Reviewmentioning
confidence: 99%
“…The translation is an investigation of the lexical, structural, grammatical, situation, the context of the culture in the original text, then analyzing them to get the meaning, finally reconstruct them in the same meaning in the target text. Siregar et al (2018) have concluded that translation is an activity and study on transferring a formal and informal passage of text from the source language to the target language. Newmark (1988) has stated that there are some translation methods, such as word-for-word translation, literal translation, faithful translation, semantic translation, adaptation, free translation, idiomatic translation, and communicative translation.…”
Section: St: Dikeluarkannya Resolusi-resolusi Dewan Keamanan Pbb Tt: mentioning
confidence: 99%